(untitled) (Jurnal Ipteks Terapan, 2022)
This observation was conducted in order to determine the effect of capital structure, firm growth, firm size and profitability on firm value. The results of the t-test in this study show that only profitability has a significant effect on firm value. The results of the f test on this observation indicate that the capital structure, firm growth, firm size and profitability do not simultaneously affect firm value